"Family Matters": A Systematic Review of the Evidence For Family Psychoeducation For Major Depressive Disorder. (16th November 2016) - Brady, Pamela; Kangas, Maria; McGill, Katherine
Abstract : The first aim of this systematic review was to evaluate the evidence for family psychoeducation (FPE) interventions for major depressive disorder (MDD). A second aim was to compare the efficacy of different modes of delivering face‐to‐face FPE interventions. Ten studies (based on nine distinct samples) were identified comprising four single‐family studies, four multifamily studies, one single versus multifamily comparative study, and one peer‐led, mixed‐diagnosis study. Seven studies measured patient functioning and six reported positive outcomes. Six studies measured carer's well‐being and four reported positive outcomes. Results provide preliminary evidence that FPE leads to improved outcomes for patient functioning and family–carer's well‐being for persons with depression. The implications for future development and delivery of FPE interventions for MDD are discussed.